Compreendendo o ser doente renal crônico - Barbosa, Jaqueline Caracas (1993)
This study is lhe result of my inquietude in relationship to the ill person with renal chronic ilness that is submit to dialysis procedure. For that, I used qualitative research - phenomenological modality, that allowed me to understand the ill and to answer my interrogation: "WHAT IS TO BE A RENAL CHRONICALLY ILL PERSON?" The analysis of descriptions, the search for the meaning of their iived experiences revealed that for those subjects, to be a chronically ill means to experience a sudden change in life, to think about death and to remember the impact experienced in the moment that the diagnosis was first revealed. It signifies also to live with limitations, with hemodialysis treatment that is painful, and consuming for the body although essential for life. Those persons live also with the possibility of having a kidney transplant, and with the expectation of a better quality of life. This comprehension allow new horizons of assistance to the renal chronically ill by professionals that take care of them.